Possibilities of installation of lateral (disk) implants in cases of distal mandibular atrophy: results of own clinical experience - Vares Я. Е.; Hudzan Я. С.; Student В. О.; Filipska Т. А.; Vares Я. Я. (Actual Dentistry, 2021)
Distal mandibular aspects, especially in conditions of atrophy of the alveolar processes, are traditionally considered unfavorable for dental implantation, which is primarily due to unsatisfactory anatomical and topographic peculiarities (proximity of the inferior alveolar nerve, presence of the mandibular fossa) and require on the pre-implant preparation stage a row of additional surgical procedures aimed on increasing of bone volume or an employment of alternative implantation techniques. Aim – summarizing of own experience of placement of lateral (disc) implants in cases of severe distal mandibular atrophy. Materials and methods. 10 patients (men – 3, women– 7) with uni-, bilateral free-end defects or total mandibular adentia were examined and treated. 22 lateral (disc) implants BOI® (Ihde Dental AG, Switzerland) were installed in combination with 1-stage screwable compression implants KOS®, TPG® Uno (Ihde Dental AG, Switzerland) and loaded immediately within 3–4 days. Results. On the control clinical and roengenological inspections 6-9 mo post-op 20 (90.9 %) of 22 installed lateral (disc) were stable, painless at percussion, with absence of evident inflammation around them, demonstrating the signs of osteointegration. There was no one case of complications due to direct mechanical damage of mandibular canal walls by disc components of the implants. Conclusions. Placement of lateral (disc) implants in distal mandibular aspects creates a serious alternative to generally recognized techniques of pre-implant surgery, allows to provide a functional status of dento-maxillary system in shortest terms owing to realization of their immediate loading protocol.